2017
DOI: 10.1007/s11368-017-1725-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the reverse seasonal flooding on soil texture within the hydro-fluctuation belt in the Three Gorges reservoir, China

Abstract: Purpose The formation of the large hydro-fluctuation belt at the altitude of 145-175 m, following the construction of the Three Gorges Dam, developed from the terrestrial system in the Three Gorges reservoir. This research mainly concerned the effects of the resultant reverse seasonal flooding on soil texture. Materials and methods Four field experimental plots were designed with sample belts and quadrats at the head, middle, and tail sections of the reservoir area. Stratified soil samples were collected, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 19 publications
(23 reference statements)
2
15
0
Order By: Relevance
“…Responses in branch and leaf functional traits to the water level gradient Water level uctuations are important ecological processes that in uence the ecosystem in water leveluctuating regions (Matthew et al, 2019). Under the in uence of water level uctuations, the ecological environment at the water level-uctuating region exhibits clear spatial heterogeneity, where environmental factors including emergence period, emergence time and soil water content are signi cantly different across the water level conditions (Wang et al, 2018). Caused by the environmental heterogeneity, branch and leaf growth traits of riparian plants also exhibit spatial variations across the water level conditions (Spencer et al, 2004;McCoy-Sulentic et al, 2017;Duan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses in branch and leaf functional traits to the water level gradient Water level uctuations are important ecological processes that in uence the ecosystem in water leveluctuating regions (Matthew et al, 2019). Under the in uence of water level uctuations, the ecological environment at the water level-uctuating region exhibits clear spatial heterogeneity, where environmental factors including emergence period, emergence time and soil water content are signi cantly different across the water level conditions (Wang et al, 2018). Caused by the environmental heterogeneity, branch and leaf growth traits of riparian plants also exhibit spatial variations across the water level conditions (Spencer et al, 2004;McCoy-Sulentic et al, 2017;Duan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…When the water level gradually decreased in early September, M. laxi ora plants emerged and quickly restored their vegetative growth, and then began to ower and set fruits within a week (Chen and Xie, 2009). After the construction of the Three Gorges-Gezhou Dam cascade hydropower station, because human regulation on river discharge is conducted to ful ll the needs of ood prevention and power generation, the water level uctuation pattern in the habitat of M. laxi ora remnant populations was signi cantly altered: the emergence time of habitats is delayed, average periods of emergence was shortened from 220 days to 190 days; the ooding retreat rapidly during the growth restart period; also, and the water level in the winter dry season dramatically decreased (Wang et al, 2018;Duan et al, 2016;Sun et al, 2007). We investigated the branch and leaf growth traits in populations across a water level condition during the growth restart period after emergence to understand the pattern of branch and leaf growth traits changing with water level gradient and the phenotypic plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Remnant M. laxiflora populations exist between 41 and 46 m altitude. The soil type of this site is Haplic Alisol (depth, 30–40 cm), the soil organic matter content ranged 10.0–16.0%, and the soil bulk density and porosity ranged 35.52–61.81% and 1.05–1.81 g cm −3 , respectively (Chen, Guan, et al, ; Chen, Wu, et al, ; Chen & Xie, ; Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Water submergence can also reduce the input of fresh OC from plant litter and root exudates because of less oxygen availability for plant roots 35 . Meanwhile, enzyme activities could be indirectly affected by soil pH and microclimates under large hydroelectric project 1,5,36 . For instance, Amendola et al 5 have found that increase in soil moisture results in higher enzyme activities, with soil becoming dry condition, the substrate diffusion and oxygen content can limit enzyme activities.…”
mentioning
confidence: 99%
“…Since the completion of the Three Gorges Dam in 2008, a total area of 350 km 2 water level fluctuation zone has been formed in the Three Gorges Reservoir with water level fluctuation from 145 m above sea level in summer (May to September) to 175 m in winter (October to April) 1,38 . The reversal of submergence time and prolonged inundation dramatically lead to change in soil moisture, pH and vegetation types 32,34 , and these changes ultimately affect soil C cycling and enzyme activities.…”
mentioning
confidence: 99%